Prescription and predictors of post‐stroke antidepressant treatment: A population‐based study. (24th April 2018) - Mortensen, J. K.; Johnsen, S. P.; Andersen, G.
Abstract : Objectives: Post‐stroke depression and pathological crying are common and potentially serious complications after stroke and should be diagnosed and treated accordingly. Diagnosis and treatment probably rely on clinical experience and may pose certain challenges. We aimed to examine prescription and predictors of antidepressant treatment after ischemic stroke in a clinical setting. Materials and methods: In this registry‐based follow‐up study, consecutive ischemic stroke patients were identified from the Danish Stroke Registry, holding information on antidepressant treatment during admission in Aarhus County from 2003 to 2010. Information on prescription after discharge was obtained from the Danish Prescription Database. Treatment initiation was analyzed using the cumulative incidence method including death as a competing risk. Multiple logistic regression was used to identify potential predictors of treatment. Results: Among 5070 consecutive first‐ever ischemic stroke patients without prior antidepressant treatment, the cumulative incidence of antidepressant treatment and prescription over 6 months was 35.2% (95% CI: 33.8‐36.6). Overall 16.5% (95% CI: 15.5‐17.6) started treatment within 14 days corresponding to 48.1% (95% CI: 45.8‐50.5) of all treated patients, and the most widely prescribed group of antidepressants was selective serotonin reuptake inhibitors (86%). Increasing stroke severity was associated with higher odds of initiating treatment. Conclusion: Antidepressant treatment in this real‐life clinical setting was common and initiated early, in almost half the treated patients within 14 days. Our results suggest that special focus should be given to the severe strokes as they may have a greater risk of requiring treatment.